Characteristics of Disability Due to Ophthalmological Complications of Diabetes Mellitus - Jamalova, Shirin Abdumuratovna (International Journal of Psychosocial Rehabilitation, 2020)
Objective: To study the characteristics of primary and repeated disability due to ophthalmological complications of diabetes in Tashkent in 2003-2012. Materials and methods: A copy of 347 certificates was examined for people with ophthalmological complications of diabetes in Tashkent over 10 years. Results: The proportion of people first recognized as disabled on average for 10 years is 0.55 people with disabilities per 100 thousand people per year, the number of 1.8 people who are repeatedly recognized as disabled is 0.97. The general level of disability is generally not high - 1.53; severe disability prevails - I and II groups, including among primary disabilities. In the structure of both repeated and primary disabilities, the number of people of middle and retirement age prevails, but in the group with re-recognized disability, the number of young people with disabilities is 4.5 times more than in the group with newly established disability. Conclusion: The level of disability due to ophthalmological complications of diabetes is not high, however, among persons recognized as such in both groups, people with disabilities of groups I and II prevail, requiring more social support; among disabled people, middle-aged people predominate - the able-bodied population, which also causes economic damage.